Carbon assessment of a wooden single-family building – A novel deep green design and elaborating on assessment parameters. (1st April 2023) - Petrović, Bojana; Eriksson, Ola; Zhang, Xingxing
Abstract: The aim of this study was to investigate how the carbon accounting of a wooden single-family house is affected by (1) decreasing the carbon footprint by changes in building design, (2) differentiating biogenic carbon from fossil carbon and (3) including external benefits beyond the state-of-the-art system boundaries. The motivation of exploring different system boundaries, improved building design and investigating benefits aside of system boundaries rely on the fact of having the "full" picture of GHG emissions of building products. Changes in building design were analyzed by life cycle assessment (LCA) focusing on greenhouse gas (GHG) emissions, while the costs were assessed by using lice cycle cost (LCC). The findings showed that by including positive and negative emissions from the production phase for an improved building design within scenario 4 'Cradle to Gate + Biogenic Carbon + D module' has the lowest embodied GHG emissions when compared to other approaches with −3.5 kg CO2 e/m 2 /y50 . Considering the impacts of the whole building, the lowest GHG emissions are within the scenario 8 'Cradle to Grave + Biogenic Carbon + D module' for the improved building design with −0.7 kg CO2 e/m 2 /y50 . The results suggest that a change to sustainable alternatives for building components that makes the whole building to be constructed by wood, could lead to significant reduction of GHG emissions compared to conventional material choices. Economically, testing sustainable solutions, the highlighted results are the construction costs that are almost double higher for CLT elements for the foundation compared to concrete. Highlights: The study represents "full" picture of GHG emissions by considering stored and released CO2 e emissions of building products. Cradle to Gate and Cradle to Grave system boundaries including biogenic carbon and external benefits provide a real estimate of GHG emissions in buildings. Biogenic accounting is important method for calculation of absorbed GHG from wooden products. Wood-based building materials lead to significant reduction of GHG emissions.